2017
DOI: 10.1007/s00105-017-3971-y
|View full text |Cite
|
Sign up to set email alerts
|

Ulkus bei Adipositas-assoziierter chronischer Veneninsuffizienz

Abstract: The cause of obesity-associated chronic venous insufficiency has been associated with an increased intraabdominal pressure due to abdominal fat masses. It leads to venous hypertension. Therapy consists of consequent compression therapy combined with suitable wound care, weight reduction, and regular exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…Interesting to note is that just every second (56%) of the sample received self-care advice on physical activity at the same time, it seems that this measure has no significant impact on healing time. Nevertheless, physical activity can be beneficial in terms of the influence of weight loss which can have a positive relation to ulceration [58] since patients with obesity are at higher risk for VLUs [22]. Furthermore, an activation of calf muscles facilitates the venous reflux [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Interesting to note is that just every second (56%) of the sample received self-care advice on physical activity at the same time, it seems that this measure has no significant impact on healing time. Nevertheless, physical activity can be beneficial in terms of the influence of weight loss which can have a positive relation to ulceration [58] since patients with obesity are at higher risk for VLUs [22]. Furthermore, an activation of calf muscles facilitates the venous reflux [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Having established the severity of venous disease in our cohort, we then sought to determine whether this was correlated with obesity. In fact, the correlation between obesity and venous disease is somewhat controversial, with several studies confirming a positive correlation 19–21 and coining the term “phlebesity”, 22 while other studies have failed to replicate this finding 19,23 . Patients with grade 3 obesity had severe leg symptoms, typical of chronic venous insufficiency, but approximately two‐thirds of the limbs had no anatomical evidence of venous disease.…”
Section: Discussionmentioning
confidence: 99%
“…caused by peripheral arterial disease, diabetes mellitus, or malignancies [20]. Though not showing any vein obstruction or reflux at ultrasonography, obese patients (stage 1-3 = BMI 35-≥ 40) can develop VLUs, indicating a correlation between CVD and obesity because of increased intraabdominal pressure [21]. It was confirmed that obesity contributes to hindered venous backflow [22].…”
Section: Vein and Tissue Physiology And Pathophysiologymentioning
confidence: 99%